Chronology of the Pueblo Viejo epithermal gold-silver deposit, Dominican Republic: formation in an Early Cretaceous intra-oceanic island arc and burial under ophiolite. - Mueller, A.; Hall, G.; Nemchin, Alexander; O'Brien, D. (Springer, 2008)
The Pueblo Viejo deposit (production to 1996:166 t Au, 760 t Ag) is located in the Dominican Republic on the Caribbean island of Hispaniola and ranks as one of the largest high-sulfidation/acid-sulfate epithermal deposits (reserves in 2007: 635 t Au, 3,648 t Ag). One of the advanced argillic ore bodies is cut by an inter-mineral andesite porphyry dike, which is altered to a retrograde chlorite-illite assemblage but overprinted by late-stage quartz-pyrite-sphalerite veins and associated low-grade Au, Ag, Zn, Cd, Hg, In, As, Se, and Te mineralization. The precise TIMS U-Pb age (109.6±0.6 Ma) of the youngest zircon population in this dike confirms that the deposit is part of the Early Cretaceous Los Ranchos intraoceanic island arc. Intrusion-related gold-sulfide mineralization took place during late andesite-dacite volcanism within a thick pile (>200 m) of carbonaceous sand- and siltstones deposited in a restricted marine basin.The high-level deposit was shielded from erosion after burial under a late Albian (109-100 Ma) ophiolite complex (8 km thick), which was in turn covered by the volcano-sedimentary successions (>4 km) of a Late Cretaceous-Early Tertiary calc-akaline magmatic arc. Estimates of stratigraphic thickness and published alunite, illite, and feldspar K-Ar ages and closure temperatures (alunite 270±20C, illite 260±30C, K-feldspar 150C) indicate a burial depth of about 12 km at 80 Ma. During peak burial metamorphism (300C and 300 MPa), the alteration assemblage kaolinite + quartz in the deposit dehydrated to pyrophyllite. Temperature-time relations imply that the Los Ranchos terrane then cooled at a rate of 3-4C/Ma during slow uplift and erosion.